1997
DOI: 10.1097/00004728-199705000-00006
|View full text |Cite
|
Sign up to set email alerts
|

CT Patterns of Nodular Hepatic and Splenic Sarcoidosis: A Review of the Literature

Abstract: We conclude that increased awareness and recognition of these patterns of nodular hepatic/splenic sarcoidosis on CT will greatly improve detection and diagnosis of abdominal sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 11 publications
0
32
0
1
Order By: Relevance
“…Splenic involvement is conrmed in 24 to 59z of patients by biopsy 7,8 and in 38 to 77z of patients by autopsy, 9 and one previous study showed splenic lesions in 69z of patients with hepatic sarcoidosis. 10 Hepatosplenic sarcoidosis most commonly manifests as organomegaly. 11 Five to 15z of patients have multiple nodules in the liver and spleen observable on MR imaging (Fig.…”
Section: Hepatosplenic Sarcoidosismentioning
confidence: 99%
“…Splenic involvement is conrmed in 24 to 59z of patients by biopsy 7,8 and in 38 to 77z of patients by autopsy, 9 and one previous study showed splenic lesions in 69z of patients with hepatic sarcoidosis. 10 Hepatosplenic sarcoidosis most commonly manifests as organomegaly. 11 Five to 15z of patients have multiple nodules in the liver and spleen observable on MR imaging (Fig.…”
Section: Hepatosplenic Sarcoidosismentioning
confidence: 99%
“…In a biopsy-proven study of 49 patients, LAP in 20 of the cases, splenomegaly in 16 of them, hepatomegaly in two and hypodens nodular lesions in spleen and liver in seven of the patients were reported (11). In a review consisted of 20 patients who had splenic and hepatic hypodense lesions, isolated splenic spread is in seven patients, isolated hepatic spread is in 4 and both hepatic and splenic spread simultaneously was seen in nine patients (12). Multiple hepatic and splenic involvement of sarcoidosis in 39 cases and isolated splenic involvement were reported in only three cases in English literature (5).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of frequent hepatosplenic involvement, abdominal imaging studies usually show only a nonspecific heterogeneous hepatosplenomegaly. The presence of nodules in the liver and spleen on sonography and CT is unusual 4,6,[8][9][10] and has been reported in only 5% of hepatic sarcoidoses and 15% of splenic sarcoidosis. 10,11 The detection of hepatic or splenic focal lesions, as in our case, triggers a wider differential diagnosis that includes other conditions such as metastatic disease and lymphoma.…”
Section: Discussionmentioning
confidence: 99%